Complications of Acute Rhinosinusitis: A Study on Orbital and Intracranial Manifestations at a Tertiary Care Hospital in Pakistan - Muhammad Umer Khan Khalil, Rehan Moinuddin Shaikh, Muhammad Irfan Khan, Ahsan Qureshi, Wing Commander Muhammad Tahir Shah, Mohammad Aamir Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute rhinosinusitis can lead to severe complications, particularly orbital and intracranial manifestations, which require timely diagnosis and management. This study evaluates the prevalence, risk factors, microbiological spectrum, and outcomes of such complications at a tertiary care hospital in Pakistan. Methods: A retrospective cohort study was conducted at Jinnah Postgraduate Medical Center and Sir Syed Hospital, Karachi, from January 2021 to December 2023. A total of 220 patients with clinically and radiologically confirmed acute rhinosinusitis and associated complications were included. Data on demographics, comorbidities, symptom duration, microbiological findings, treatment modalities, and clinical outcomes were analyzed. Orbital complications were classified into preseptal cellulitis, orbital cellulitis, subperiosteal abscess, orbital abscess, and cavernous sinus thrombosis. Intracranial complications included epidural abscess, subdural abscess, brain abscess, and meningitis. Statistical analyses were performed using SPSS version 26, with logistic regression applied to determine risk factors for severe complications. Results: Orbital complications were observed in 135 (61.4%) patients, while 85 (38.6%) had intracranial complications. Patients with intracranial involvement had significantly longer symptom durations (p < 0.001). The most common orbital complication was preseptal cellulitis (32.6%), whereas epidural abscess (28.2%) was the most frequent intracranial manifestation. Streptococcus pneumoniae (36.2%) and Staphylococcus aureus (28.3%) were the predominant pathogens. Medical management alone was sufficient for 102 (46.4%) patients, while 118 (53.6%) required surgical intervention. Patients with intracranial complications had longer hospital stays (p < 0.001) and higher rates of neurological sequelae (p < 0.001). Mortality occurred in 5 (5.9%) patients with severe intracranial infections. Conclusion: Orbital and intracranial complications of acute rhinosinusitis pose significant morbidity risks. Prolonged symptom duration and diabetes mellitus were associated with increased severity. Early diagnosis, targeted antimicrobial therapy, and timely surgical intervention are crucial for improved outcomes. Keywords: Acute rhinosinusitis, orbital complications, intracranial complications, sinus infection, tertiary care hospital.